The Role of Teacher in Industry 5.0, Technology, and Social Capital in for Vocational High School Graduates in School-to-Work Transitions - Utami, Pipit; Fajaryati, Nuryake; Sudira, Putu; Ismail, Mohd Erfy; Maneetien, Nopadon; Felestin, Felestin (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
The large number of graduates who lack the skills needed for the workplace makes it difficult for them to find employment. This study aims to analyze the influence of teachers, technology, and social capital in preparing vocational school graduates for their first jobs. Participants came from five districts in Yogyakarta, including state and private VHS with engineering expertise, including 25 teachers and 99 students. The research steps involve conducting literature reviews, focus group discussions, and data collection via questionnaires. The results show that: (1) the stability of choosing a career that is in line with their education for graduates who study further is better than graduates who work or are entrepreneurs; (2) the measurement model showed valid and reliable results: outer loading (0.702 -0.967), AVE ³ 0.5, Cronbach's alpha ³ 0.7, Fornell-Larcker criterion, and HTMT ratio. The structural model using the SRMR is 0.078 (good fit); (3) With p-value 0.000 (sig < 0.05), there is direct significant influence between TCR -> TGR (f2 0.897), TCR -> SCR (f2 0.638) with large effect, and TCR -> STWT (f2 0.310), TGR -> STWT (f2 0.189), SCR -> STWT (f2 0.267) with medium effect and the indirect influence (TCR -> STWT), which is mediated by TGR and SCR. The role of the teacher (TCR) has a significant impact on optimizing the role of technology (TGR) and social capital (SCR) in the STWT effectivity. The role of teachers, technology, and social capital all have significant and medium effects on the STWT smoothness. This is in line with the concept of Industry 5.0, specifically integration. Education in the Industry 5.0 era is dependent not just on the contributors' roles but also on integration.